Social media and digital marketing for destination promotion and branding: The case study of the Can’t Skip Portugal campaign - Sevilla Castillo, Carlos (2021)
The main objective of the present case study is to approach the importance of social media and digital marketing for the destination promotion. The case of the 2017 campaign by Turismo de Portugal: Can’t Skip Portugal was used to exemplify how a destination can rely on digital marketing on social media to deliver a message that is relevant to their target market and at the same time convey a brand identity. How did the Can’t Skip Portugal Campaign managed to do this for Portugal? A deep analysis of the campaign was done to answer that question. By doing so, three main themes were identified as crucial for the success of the Can’t Skip Portugal Campaign: relying entirely on an audio-visual format that is more appealing and that easily displays Portugal attractiveness; the incorporation of a predominantly emotional message rather than plain delivery of information; and an adequately balanced message that encouraged potential tourists to take action and travel and visit Portugal, whilst at the same time conveying a brand of what Portugal is as a tourism destination. Can’s Skip Portugal can be deemed a successful example of an online digital marketing Campaign thanks to the adequate mix of the variables previously described. Undoubtedly, social media platforms will reinforce its status as the preferred method of doing digital marketing, and destination management organisations and regional tourism authorities must be vigilant and make sure that their digital marketing efforts comply with a set of parameters that will guarantee their success and effectiveness.